2003
DOI: 10.1074/jbc.m302221200
|View full text |Cite
|
Sign up to set email alerts
|

Src Regulates Golgi Structure and KDEL Receptor-dependent Retrograde Transport to the Endoplasmic Reticulum

Abstract: The tyrosine kinase Src is present on the Golgi membranes. Its role, however, in the overall function and organization of the Golgi apparatus is unclear. We have found that in a cell line called SYF, which lacks the three ubiquitous Src-like kinases (Src, Yes, and Fyn), the organization of the Golgi apparatus is perturbed. The Golgi apparatus is composed of collapsed stacks and bloated cisternae in these cells. Expression of an activated form of Src relocated the KDEL receptor (KDEL-R) from the Golgi apparatus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
97
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(101 citation statements)
references
References 24 publications
3
97
1
Order By: Relevance
“…This model is supported by the compact Golgi morphology that we observed in cells treated with PP2 and that others have observed in cells lacking Src kinase family members, such as SYF −/− cells (30). Thus, in normal cells, Src activity is expected to vesiculate the Golgi during a secretory stimulus.…”
Section: Discussionsupporting
confidence: 68%
“…This model is supported by the compact Golgi morphology that we observed in cells treated with PP2 and that others have observed in cells lacking Src kinase family members, such as SYF −/− cells (30). Thus, in normal cells, Src activity is expected to vesiculate the Golgi during a secretory stimulus.…”
Section: Discussionsupporting
confidence: 68%
“…58 Interestingly, it was also demonstrated that the exogenous expression of the constitutive-active Src (E378G) in the SYF cells affected the distribution of some if not all Golgi-specific proteins. 58 Thus, it is possible that the accumulation of the active Hck affects the structure of the Golgi and thereby perturbs the trafficking of Fms.…”
Section: Discussionmentioning
confidence: 99%
“…Circularity values vary from 1 (for a perfect circle) to 0. Values below 1 indicate an elongated or stellate cell body and/or an increasing number of cellular processes (Berezin et al, 1997;Bard et al, 2003). For graphic presentation, normalized mean values ± s.e.m.…”
Section: Image Analysismentioning
confidence: 99%